Hyperbolic problems : theory, numerics, applications : proceedings of the Ninth International Conference on Hyperbolic Problems held in CalTech, Pasadena, March 25-29, 2002 - International Conference on Non-linear Hyperbolic Problems (9th : 2002 : Pasadena, Calif.); Hou, Thomas Y.; Tadmor, Eitan (New York : Springer, 2003)
41